Unique para-effect in electron ionization mass spectra of bis(perfluoroacyl) derivatives of bifunctional aminobenzenes() - Tretyakov, Kirill V. (Rapid Commun Mass Spectrom, 2010)
A new kind of ‘para-effect’ under electron ionization (EI) conditions has been discovered for a series of bis(perfluoroacyl) derivatives of o-, m- and p-phenylenediamines, -hydroxybenzeneamines and -mercaptobenzeneamines of a common structure RCOX–C(6)H(4)–NHCOR (X = NH, S, O; R = CF(3), C(2)F(5), C(3)F(7)). Only the para-isomers showed successive loss of a radical RCO(•) and a molecule RCN, leading to very intense peaks in the EI spectra. The composition and the origin of the [M–COR–NCR](+) ions were confirmed by exact mass measurements and linked scan experiments. The proposed mechanism of their formation takes into account likely para-quinoid structures of the precursor ions. A similar rearrangement has not been observed for para-isomers in the series of bis(perfluoroacyl) derivatives of benzenediols, mercaptophenols and dimercaptobenzenes.